Numerical and experimental research on unsteady cavitating flow around NACA 2412 hydrofoil. Issue 2 (15th January 2015) - Sedlář, M; Komárek, M; Rudolf, P; Kozák, J; Huzlík, R
Abstract: This work deals with the numerical and experimental investigation of unsteady cavitating flow around a prismatic NACA 2412 hydrofoil. The main attention is focussed on the dependence of cavitation dynamics on the cavitation number at high incidence angles. The experimental research is carried out in the cavitation water tunnel the rectangular test section of which has inner dimensions 150×150×500 mm. Currently tested hydrofoils have a chord length of 120 mm and are equipped with pressure transducers at the leading edge and on the suction side. The PVDF hydrophone enables to measure high-frequency pressure pulses behind the hydrofoil trailing edge. The visualizations are based on two simultaneous high-speed cameras, recording the hydrofoil from the top and from one side. A comprehensive CFD analysis has been done with the ANSYS CFX package for a wide range of flow regimes. Different turbulence models including SAS-SST and Reynolds-stress models have been tested to capture highly unsteady phenomena on the hydrofoil. The numerical simulations show, that the dominant frequency of the cavity oscillation depends on the cavitation number and that there is a certain range of this number in which the "resonance" effect can be reached. In such regime the amplitudes of the pressure pulses on the suction side of the hydrofoil dramatically increase. The calculated results have been verified by both the visualizations and the pressure measurements carried out at the hydrofoil incidence angle of 8 degrees.